A COMPARATIVE STUDY ON MAGUINDANAON TRADITIONAL MARRIAGE AND ISLAMIC MARRIAGE SYSTEM - Butuan, Omar; Abellar, Elisa; Mayasa, Samsiya; Blah, Sadat G.; Fiesta, Margie; Kasim, Osmeňa (Advances in Social Sciences Research Journal, 2021)
This study aimed to find out the Comparison of the Maguindanaon Traditional Marriage and the Islamic form of Marriage. Specifically, the study seeks to find out the Socio-demographic profile of the respondents in terms of age, sex, Marital Status and educational attainment. The Requisites of the Maguindanaon Traditional form of Marriage and the Requisites of Islamic forms of Marriage are identified in this study. Also, the factors to a successful marriage in terms of Cultural / familial, Economic, Spiritual factor and the difference between the Maguindanaon Marriage and that of the Islamic Marriage system are the focused of this study. This study made use of expost facto research design particularly descriptive ethnographic in approach. This study was conducted in the thirty four barangays of municipality of Datu Odin Sinsuat, Maguindanao. The respondents of this study were individuals who have sufficient information on Traditional Marriage of the Maguindanaon and Islamic form of Marriage. There were 200 respondents for the entire municipality. 100 respondents are those members of the Al-Hiqma organization, and one hundred (100) respondents were from Maguindanaon local folk who had sufficient information about Maguindanaon traditional marriage, and used the simple random sampling procedures. A survey questionnaire was used for the respondents who can read and write and for the respondents who have no knowledge on reading and writing used interview method. Based on the findings of the study, the beliefs and practices of the Maguindanaon in terms of marriage were handed to them by their forefathers through series of generations down to present. These beliefs and practices were counted as legacies of the past that remained a living heritage of the present generations. The Maguindanaon tradition on marriage is still primitive in many aspects like the negotiation of third parties, imposition of dowry, man’s servitude to his in-laws and many of the rituals of the past are still seen in the present time. Education, both Islamic and Western have influenced the marriage practices of some Maguindanaons in the urban society as some of their marriage ceremony are held in hotels and restaurants. The augmentation of the materialistic nature of maguindanaon traditional marriage has been maintained and increased due to the devaluation of the Philippine currencies. Key words: Comparative Study, Maguindanaon, Traditional Marriage, Islamic Marriage System